Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.phro.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of manual adjustment performed in clinical practice following deep learning contouring for head and neck organs at risk in radiotherapy

Abstract: Background and purpose: Auto-contouring performance has been widely studied in development and commissioning studies in radiotherapy, and its impact on clinical workflow assessed in that context. This study aimed to evaluate the manual adjustment of auto-contouring in routine clinical practice and to identify improvements regarding the auto-contouring model and clinical user interaction, to improve the efficiency of auto-contouring. Materials and methods: A total of 103 clinical head and neck cancer cases, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…For the heart and esophagus, the Lung DL-model was used. The thyroid was taken from a head-and-neck DL-model [15] . The esophagus and thyroid were included when periclavicular or parasternal lymph node regions were involved.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the heart and esophagus, the Lung DL-model was used. The thyroid was taken from a head-and-neck DL-model [15] . The esophagus and thyroid were included when periclavicular or parasternal lymph node regions were involved.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of automatic contouring has been widely studied on the geometrical level by comparing automatic delineations and user-adjustments, but typically using whole-organ measures and performed mostly on a limited patient cohort. A more extended analysis was previously published for head & neck cancer patients by Brouwer et al [15] . This current study aimed to evaluate the extent of manual adjustments following auto-contouring of organs-at-risk (OARs) in the thorax region in clinical practice for a large patient group.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to [5], we observed that many time consuming contour adjustments were minor changes along the boundary which are in many cases unlikely to have a large impact on dose. We agree with [5] that there is a need for methods that guide delineators in determining which corrections are meaningful for dose-planning. The combination of electronic health records, stored dose matrices and CT scans from record and verify systems has great potential to increase our understanding of radiation dose effects for normal tissues [59].…”
Section: Discussionmentioning
confidence: 59%
“…14,15 Prospective studies have shown that in carefully controlled situations, automated treatment planning (ATP) generates plans of comparable or better clinical quality, at significant time savings. [16][17][18] A variety of commercially available automation tools exist, including but not limited to atlas-based 19 and deep-learningbased 13 auto-contouring (AC), knowledge-based planning (KBP), 20 rule-based automated planning, 21 and automated field-in-field planning. 22 However, little is known about the scale of clinical implementation of ATP techniques in the United States.…”
Section: Introductionmentioning
confidence: 99%